Emerging from the Experiment: A Systematic Methodology for Creative Writing Teaching. - Smith, Hazel (New Writing: The International Journal for the Practice & Theory of Creative Writing, 2006)
This paper argues for a particular teaching methodology for creative writing that produces a multilayered poetics of writing. This methodology is the basis for my book The Writing Experiment: Strategies for Innovative Creative Writing, and is specifically designed for higher-education creative writing students, though it can be used by others. The methodology conceptualises the process of writing as systematic, and breaks it down into incremental stages that nevertheless have open-ended outcomes. It emphasises experimental writing and a politics and ethics of form; it also uses literary and cultural theory to theorise the process of writing. In addition it approaches writing as an endeavour that extends beyond the written page into performance and new media work. All these different aspects of the methodology are interrelated and overlapping. In this paper I elucidate contexts and specifics of these different approaches, and show how they are integrated so that they reverberate with, and extend, each other.